Nutritional supplementation and its association with health and body composition of bodybuilding practitioners (Research, Society and Development, 2020)
This quantitative study aimed to analyze the consumption nutritional supplements in an academy in the Castanhal-PA city, as well to evaluate the anthropometric changes caused by the dietary reeducation the subjects studied. Twenty individuals, 10 men and 10 women, aged between 20 and 35 years, participated in this study. Two recall questionnaires were applied, one about how the individual was fed before starting his training period and one about his feeding after three months by training, and a third questionnaire related the dietary supplementation. The results showed significant improvements in the subjects' dietary reeducation. As for dietary supplementation, the most consumed supplements were the rich in proteins (60% to men and 83% to women) and branched amino acids, which are consumed by 30% to men and 67% to women. Most supplements were consumed on their own initiative for 38% of men. The observed and reported benefits with supplementation were strength and muscle mass gain - in which 50% of men and 60% of women had these gains. Being that also a minority of the sample reported some side effects that were associated with the food supplement. Positive changes in anthropometry were also observed. It was concluded that there is a strong relation between physical exercises and changes in eating habits, and the association with the use of dietary supplements.